FUNERAL RITE AS A SOURCE FOR STUDYING IDEOLOGICAL CONCEPTS OF THE DAGESTAN POPULATION OF THE MIDDLE BRONZE AGE - Ataev, Gamzat Dibirovic; Ahundov, Tufan Isaak-oglu (History, Archeology and Ethnography of the Caucasus, 2021)
The article reviews the study of burial rituals of the Middle Bronze Age as a key source for studying ideological beliefs of the Dagestan population. The burial ritual is a major ethnographic characteristic and conservative element of an archeological culture. Along with funerary equipment, it is considered to be a reliable source for identifying features of a culture, its chronology and boundaries. The aim of the research is the study of the funeral rites of the Dagestan population of the Middle Bronze Age on the basis of analysis of burial sites, the study of which allows us to identify various religious beliefs and rituals of the cult nature of the local population. Fundamental shifts in the development of the culture of Dagestan at the turn of the Early and Middle Bronze Age led to the cultural transformation of the region and caused changes in the ideological ideas of the local population, which was reflected in the funeral rites. This led to an increase in ethnic diversity, mobility of the population, the spread of the burial mound rites, cromlechs around burial structures, the appearance of burials in log cabins and carts, the use of ocher, pebble, tree-reed bedding in the funeral rite, etc. All these facts indicate a wide variety of funerary rites. These events are associated with the significant influence of the steppe tribes on the culture and ideological ideas of the local ones. A comprehensive study of burial structures and rituals of the population of Dagestan in the Middle Bronze Age made it possible to highlight many issues associated with ideological ideas and social organization of the society, ethnocultural contacts of the local population with neighboring tribes. The study of material of burial sites allows to get an idea of the spiritual culture of the population of the region under consideration: to reveal the fact that the population of Dagestan in the Middle Bronze Age had complex and varied beliefs, among which were ideas about the “soul”, “afterlife”; magic and protective actions, animal cults, nature and other cosmological ideas, which were also of great importance.